“A Numerical Investigation Into The Thermal Distribution In A Steam Cracking Furnace” Optimal Chemicals (M) Sdn. Bhd. Case Study - Khairil Fadzli Bin Abu Bakar, Khairil Fadzli (Universiti Teknologi Petronas, 2010)

(untitled)
This project is about a Radiant Tube Coil bending problem inside a Furnace Firebox. This Radiant Tube Coil Bend problem study is crucial because it may affect the reliability life of the radiant tube coil inside the furnace. However, based on the RCI, there are assumptions made that may cause this failure such as non uniform heat distribution inside the firebox, malfunction of the counterweight system for the radiant coil, or too much heat supply.